Danger sound Klaxon : the horn that changed history - Jordan, Matthew F. (University of Virginia Press, 2023)
"Danger Sound Klaxon tells the story of the Klaxon automobile horn, one of the first great electrical consumer technologies of the twentieth century, and it examines the problem of using sound to communicate in an increasingly noisy automobile-centered modernity. By charting the rise and eventual fall of the Klaxon, the author highlights how perceptions of sound-producing technologies are guided by and transform due to public debate, consumer discourses, and governmental regulations"--